Efficacy of Chamomile Mouthwash on Clinical And Serum Inflammatory Parameters in Relation to Chlorhexidine in Chronic Gingivitis Patients - Ahmed Baban , Dilyar (Diyala Journal of Medicine, 2021)
Background: Oral and systemic infections are closely linked to poor oral hygiene. Chlorhexidine mouthwash, in addition to tooth brushing has been commonly recommended. About the fact that there is a lot of studies on the effectiveness of chamomile as an herbal mouthwash, there isn't much evidence on its competitive effect with chlorhexidine. Objective: To determine the clinical and inflammatory effects of chamomile as mouthwash (MTC) in the treatment of chronic gingivitis and compare its effect with 0.12% chlorhexidine (CHX). Patients and Methods: A total of 45 subjects aged 18-45 years with chronic gingivitis underwent scaling and polishing with oral hygiene instruction; 15 patients received 1% of (MTC) as mouthwash, 15 patients received 0.12% of chlorhexidine mouthwash, and 15 patients received scaling and polishing only (SRP). Mouthwash was twice daily for 14 days. At the start of the study, clinical periodontal parameters (PI, GI, and BOP) and blood samples were taken and after four weeks of treatment to estimate the levels of C-reactive protein (CRP), alkaline phosphatase (ALP) and total protein (TP). Results: After 4 weeks of periodontal treatment, there was a significant decrease in clinical periodontal parameters (P<0.01) and inflammatory markers (P<0.05) in the MTC and CHX and S&P alone groups. From periodontal treatment, there was no significant difference between the MTC and CHX groups with clinical periodontal parameters and inflammatory markers (P<0.05), although there was a significant difference between the MTC, CHX groups, and the S&P alone group in terms of clinical periodontal parameters and inflammatory markers (P<0.05). Conclusion: Chamomile has been shown to be comparable to CHX in terms of reducing gingivitis by decreasing clinical periodontal parameters and inflammatory chemical markers values such as CRP, ALP, and TP.